Targeting Neurological Manifestations of Coronaviruses by Candidate Phytochemicals: A Mechanistic Approach - Fakhri, Sajad; Piri, Sana; Majnooni, Mohammad Bagher; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2021)
The novel coronavirus 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made a wide range of peripheral and central signs. In this regard, growing evidence is focusing on COVID-19 neurological manifestation; however, there is a lack of established pathophysiological mechanisms and related treatments. Besides, previous reports have indicated the neuroprotective effects of phytochemicals in central disorders. Accordingly, a comprehensive review was conducted, using electronic databases, including PubMed, Scopus, Web of Science, and Cochrane along with the authors’ expertise in neuronal signaling pathways, and phytochemicals effects. Considering a high homology among SARS-CoV, Middle East Respiratory Syndrome (MERS), and SARS-CoV-2, revealing their precise pathophysiological mechanisms seems to pave the road for the treatment of COVID-19 neural manifestations. There is a complex pathophysiological mechanism behind central manifestations of COVID-19, including pain, hypo/anosmia, delirium, impaired consciousness, pyramidal signs, and ischemic stroke. So, employing multi-target natural secondary metabolites seems to show a bright future. In this review, central pathophysiological mechanisms and therapeutic targets of SARS-CoV-2 has been provided. Besides, in terms of pharmacological mechanisms, phytochemicals have been introduced as potential multi-target agents in combating COVID-19 central nervous system complications.